PROBLEM-BASED LEARNING (PBL) IN TEACHING MATHEMATICS - Djurayeva Rano Kayumovna (Journals Park Publishing, 2023)
Problem-Based Learning (PBL) is an instructional approach that has gained recognition and popularity in teaching mathematics. It shifts the focus from rote memorization and procedural understanding to engaging students in authentic problem-solving activities. PBL encourages students to actively explore and construct their understanding of mathematical concepts by tackling real-world problems or challenging mathematical tasks.
Keywords: Problem-Based Learning (PBL), collaborative learning, cooperative learning, teamwork, communication skills, active participation, peer support, authentic problem solving.